Do item-writing flaws reduce examinations psychometric quality? - Pais, J. (2017)
Submitted by José Pereira (jro.pereira@gmail.com) on 2017-05-22T09:04:52Z No. of bitstreams: 1 Do item-writing flaws.pdf: 1175970 bytes, checksum: e0f906a2d72f4a4f3fd1b004da9c97c5 (MD5)